2020
DOI: 10.1002/aws2.1206
|View full text |Cite
|
Sign up to set email alerts
|

Mass and flow balances for reverse osmosis virus removal crediting with tracers

Abstract: Constituents in the feed of reverse osmosis (RO) processes pass into the product by two mechanisms: diffusion through the membrane and advection through defects in the system. While minerals and tracers pass via both mechanisms, pathogens pass only via advection. Using mass and flow balances, a rigorous model is developed to characterize the response of both viruses and tracers in RO systems. The model is used to assess several tracers being considered today. Early virus testing and the commercial requirements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…13,24 Although current RO systems achieve virus rejection higher than 4 and 5 log 10 , some degree of virus advection can occur. 25,26 Novel membranes have been intensively studied for higher virus removal efficiencies. 19,23,27–31…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,24 Although current RO systems achieve virus rejection higher than 4 and 5 log 10 , some degree of virus advection can occur. 25,26 Novel membranes have been intensively studied for higher virus removal efficiencies. 19,23,27–31…”
Section: Introductionmentioning
confidence: 99%
“…13,24 Although current RO systems achieve virus rejection higher than 4 and 5 log 10 , some degree of virus advection can occur. 25,26 Novel membranes have been intensively studied for higher virus removal efficiencies. 19,23,[27][28][29][30][31] Our intension was to develop highly efficient waterpermeable membranes based on liquid-crystalline (LC) molecular order.…”
Section: Introductionmentioning
confidence: 99%
“…16−19 Aluminum oxide (Al 2 O 3 ) in activated alumina and nanocrystalline particles forms are EPA approved for use as selenium adsorbents. 20,21 However, the adsorption capacity of alumina for selenate is 0.16−4.45 times lower than selenite, 22,23 which is problematic since selenate (Se(VI)) exists at higher concentrations than selenite in fresh water. 15,24,25 Moreover, the adsorption of oxo anions on the alumina surface is sensitive to pH.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum oxide (Al 2 O 3 ) in activated alumina and nanocrystalline particles forms are EPA approved for use as selenium adsorbents. , However, the adsorption capacity of alumina for selenate is 0.16–4.45 times lower than selenite, , which is problematic since selenate (Se­(VI)) exists at higher concentrations than selenite in fresh water. ,, Moreover, the adsorption of oxo anions on the alumina surface is sensitive to pH. , At pH 3, 1 g of alumina in 200 mL of solution adsorbs 100% of 1.25 mM selenate from solution; however, the adsorption decreases to almost 0% when the pH is 9 . In-home operators cannot decrease the pH of drinking water below 6 for remediation purposes as it renders the water undrinkable; additionally, although acidification, treatment, and then neutralizing schemes are possible, they are too complex and expensive to implement in under-the-sink applications.…”
Section: Introductionmentioning
confidence: 99%
“…A significant factor for ensuring that treatment processes achieve enough pathogen removal is the ability to monitor performance and detect failure. Trussell, Kenny, Tackaert, Pisarenko, and Trussell (2020) used a fundamental environmental engineering principle-mass balances-to evaluate the ability of tracers to detect defects in reverse osmosis (RO) systems. They concluded that the best tracers in use today can detect defects at the low end of the range of LRVs that RO systems achieve for pathogen removal and that improvements in tracers could result in additional LRV credit for RO systems.…”
Section: Introduction To the Topical Collection On Potable Reusementioning
confidence: 99%